2020
DOI: 10.1371/journal.ppat.1008566
|View full text |Cite
|
Sign up to set email alerts
|

Tn-Seq reveals hidden complexity in the utilization of host-derived glutathione in Francisella tularensis

Abstract: Host-derived glutathione (GSH) is an essential source of cysteine for the intracellular pathogen Francisella tularensis. In a comprehensive transposon insertion sequencing screen, we identified several F. tularensis genes that play central and previously unappreciated roles in the utilization of GSH during the growth of the bacterium in macrophages. We show that one of these, a gene we named dptA, encodes a proton-dependent oligopeptide transporter that enables growth of the organism on the dipeptide Cys-Gly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(70 citation statements)
references
References 73 publications
(143 reference statements)
0
69
1
Order By: Relevance
“…The genome of F. novicida does not contain a gene coding for any enzyme responsible for the conversion of cystine to cysteine. We and others have previously shown that glutathione (γ-Glutamate-cysteine-glycine or GSH) constituted a major host-derived source of cysteine for intracellular Francisella [53,54]. It should be noted that, in addition to serve as an amino acid source for protein biosynthesis cysteine (and cystine) can also be used as sources of sulfur.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The genome of F. novicida does not contain a gene coding for any enzyme responsible for the conversion of cystine to cysteine. We and others have previously shown that glutathione (γ-Glutamate-cysteine-glycine or GSH) constituted a major host-derived source of cysteine for intracellular Francisella [53,54]. It should be noted that, in addition to serve as an amino acid source for protein biosynthesis cysteine (and cystine) can also be used as sources of sulfur.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Extracellular Ggt supports a model whereby GisABCD imports Ggt cleavage products, whereas intracellular Ggt suggests GisABCD imports GSH and GSSG intact 18,19 . We used the previously described His-tagged Ggt expression vector (Ggt-His) that functionally complements the ggt::Tn mutant (Supplementary Fig.…”
Section: Ggt Hydrolyzes Gsh and Gssg γ-Bonds And Is Cell Associated A Hallmark Of γ-Glutamylmentioning
confidence: 68%
“…GSH concentrations range between 0.5 and 10 mM in mammalian tissues, making it a relatively abundant source of nutrient sulfur for invading pathogens [9][10][11][12][13][14][15][16][17][18][19][20] . In addition to Cys, GSH consists of glutamate and glycine.…”
mentioning
confidence: 99%
“…Reads with 16 bp were mapped to the Lm genome using bowtie2 ( 54 ). The scripts were used to identify reads corresponding to insertions in TA sites and tally only those insertions with reads mapping from both ends of the transposon ( 55 ). Genes were screened according to fold change and BH value (|FC|≥2, BH ≤ 0.01).…”
Section: Methodsmentioning
confidence: 99%